Optimum eicosapentaenoic acid + docosahexaenoic acid levels for farmed Atlantic salmon: closing the gap between science and commercial practice - Carr, Ian; Santigosa, Ester; Chen, Tony; Costantino, John (Frontiers in Marine Science, 2024)
The shift from fish oil to vegetable oil (VO) sources has lowered eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) levels in salmon aquafeeds. VOs are high in omega-6 and low in omega-3 essential fatty acids like EPA and DHA, crucial for fish metabolism and immunity. Algal oil (AO), with high EPA + DHA and lower omega-6 levels supports fish health and growth, but transferring lab-controlled conditions to real-world commercial farming remains a challenge. This study explored the benefits of high dietary EPA + DHA levels through a commercial farm (CF) study in Chile and a Big Data (BD) study in Norway. The CF study, involving 625,000 Atlantic salmon, compared standard feed with AO-supplemented feed. The latter resulted in improved health responses and better fillet quality. The BD study analyzed real data from 232.6 million fish, revealing that EPA + DHA levels > 8% reduce mortality variability by 21%, improve economic feed conversion ratio by 11%, and increase the likelihood of superior harvests by 27%, demonstrating productivity benefits. Both studies emphasize the advantages of feeds with EPA + DHA levels above typical industry practices, enhancing growth, health, and nutritional quality. Importantly, the BD study complements the CF study, bridging the gap between science and aquafarms, and providing evidence that diets with EPA + DHA > 8% offer biological performance benefits for farmers, regardless of farming environments.